IMPLEMENTASI NILAI-NILAI PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - Marlina Rizky Suryaningsih; Anatri Desstya (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
This study aims to describe the implementation, constraints, and solutions in cultivating Pancasila student profiles in the independent curriculum. This research was conducted at SD Muhammadiyah 22 Surakarta. This research uses a qualitative approach. Data collection techniques used are observation, interviews, and documentation. The data sources in this study involved grade 1 students, grade 1 teachers, and school principals. Data analysis techniques namely data reduction, data presentation, and conclusion. Validity test by source and technique triangulation. The results showed that the planting of Pancasila student profiles in SD Muhammadiyah 22 Surakarta was carried out through habituation and project learning. Habituation done in elementary school; including praying before and after studying, reading prayer readings accompanied by practice, reading the Koran, carrying out midday prayers in congregation, getting used to 5S (smile, greeting, greeting, polite, polite), carrying out class pickets, sharing food with friends, asking permission when leaving class, conducting question and answer during learning, and discussing. The learning project that was carried out was making salted eggs. The target of achieving the planting of Pancasila student profiles in students is 80%. Obstacles experienced by teachers and schools include parents who find it difficult to communicate, hyperactive students, and some students who are not fluent in writing. Solutions in overcoming obstacles include coordinating with parents of students, disciplining students, introducing the environment to students, Always inviting students to discuss, always reminding them to 5S (smile, greet, greet, polite, and courteous), and always playing an active role and diligent in assisting students